A Simulative Approach to Electron Conduction in Thick-Film Resistors. (1983) - Jacoboni, C.; Prudenziati, M.; Rizzi, A.
Abstract : A simulative approach to the calculation of electrical transport in thick-film resistors is presented, in which electrons are considered to hop from and to metallic grains and localized states in the glass. For concentrations of metallic grains sufficiently low and of localized states sufficiently high, a maximum in conductivity as a function of temperature is obtained due to a balance between the tendency of temperature to favour hopping and to oppose an ordered response to an external force.